Epidural anaesthesia using lignocaine, bupivacaine or a mixture of lignocaine and bupivacaine in dogs - Cruz, M. L. [UNESP] (1997)
The time to loss of interdigital reflex, duration of action, duration of muscle relaxation and cardiorespiratory effects were compared after epidural block using lignocaine, bupivacaine or a combination of lignocaine and bupivacaine in dogs. Dogs were pre-medicated with methotrimeprazine, anaesthesia was induced with thiopentone, in order to facilitate epidural puncture, and a lumbosacral epidural block was performed. Body temperature fell after pre-medication, thiopentone and epidural anaesthesia. Minimal changes were observed in arterial O2 saturation, end tidal CO2, respiratory rate, heart rate and mean arterial blood pressure. The combination of bupivacaine with lignocaine produced a shorter time to loss of interdigital reflex than bupivacaine alone, longer analgesia than lignocaine alone and longer muscle relaxation than either lignocaine or bupivacaine. The combination appeared to be the best choice when surgical time is prolonged. © 1997 Wiley. All rights reserved.